Utilization of Fly Ash and Zeolite to Reduce Chemical Oxygen Demand (COD) in Domestic Waste at the Al Ihya Ulumaddin Islamic Boarding School Cilacap - Arnesya Ramadhani; Sonya Hakim Raharjo; Retno Dwi Nyamiati (Formosa Journal of Applied Sciences, 2023)
Domestic waste is the result of waste from various human activities. An alternative to reduce domestic waste is waste filtration. The purpose of this study was to find the best time for the filtration process using fly ash and zeolite to reduce COD levels in the domestic waste of the Al-Ihya Islamic Boarding School. The filter media is composed of 5 layers, namely gravel, palm fiber, zeolite, sand and fly ash. This research stage is to find the best filtration time from variations of 0, 90, 150 and 210 minutes. The resulting filtrate was tested for color and COD levels. The results show the best filtration time is 90 minutes. The color of the waste was originally cloudy black after being filtered for 90 minutes, the color changed to clear yellow. The original COD level was 1,932 mg/L after going through a filtration process for 90 minutes, decreasing to 310 mg/L.